PERILAKU KONSUMEN DALAM MEMBELI PRODUK HALAL DI KOTA BANDUNG - Setiawan, Setiawan; Mauluddi, Hasbi Assidiki (Institut Agama Islam Negeri Padangsidimpuan, 2019)
The consumer behavior in purchasing halal products is still an interesting topic to be researched because behavior is dynamic. The purpose of this study was to determine the factors that affect consumer decision in purchasing halal food. This study explored consumer driving factors in choosing halal products in the Muslim-majority community who feel that halal products are very easy to obtain. The research method used primary data analysis using a research instrument in the form of a questionnaire distributed to 200 respondents in Bandung, Indonesia. The results of this study revealed that the religiosity factor is a significant factor in affecting consumer intention in purchasing halal products. While other factors studied, such as halal awareness, halal certification, and trust, do not affect.